Investigasi Power of the Tests terkait Non-Sample Prior Information Pada Hipotesis Satu Arah - Pratikno, Budi (Universitas Airlangga, 2015)
This research discussed investigating power of the tests that related to non-sample prior information (NSPI)on a simple linear regression for known variance on one-side hypothesis. Here, the power of the unrestricted test(UT), restricted test (RT), and preliminary-test test (PTT) are used. The method for investigating the best tests is amaximum power and minimum size. A simulation study and graphical analysis are given to make comparison of powerof the tests. The result showed that the power of the tests (UT, RT, PTT) are not really different for both types ofhypotheses (one-side maximum and minimum). The power of the PTT still lies between the power of the UT and RT(at any case), so it will be a best choice between thems.